Regioselective Synthesis of 5-Nitronaphtalene-1,4-dione Derivatives in Various Solvents and Their Characterization - Iin Narwanti; Warsi Warsi; Bidyadhar Sethy (Universitas Andalas, 2026)
Regioselective synthesis is a crucial strategy in the development of bioactive molecules, as regioisomers may exhibit distinctly different biological activities. Heterocyclic naphthoquinones are a promising class of bioactive scaffolds with potential anticancer properties that might be influenced by their regiochemical configuration. This study aimed to investigate the regioselective synthesis of 5-nitronaphthalene-1,4-dione with an amine using various solvents and to characterize the target compounds. The synthesis was initiated with the nitration of 2,3-dichloronaphthalene-1,4-dione using a mixture of HNO3/H2SO4, generating compound 2 in a moderate yield. Next, compound 2 was subsequently reacted with N, N-dimethylethane-1,2-diamine under alkaline conditions at ambient temperature, affording two regioisomeric target compounds (compounds 4 and 5). The characterization confirmed the successful synthesis of compounds 4 and 5, with findings indicating that aprotic solvents facilitated the formation of compound 4, while protic solvents slightly favored the formation of compound 5. In conclusion, the results reveal that the solvent governs regioselective synthesis of 5-nitronaphthalene-1,4-dione derivatives, providing a basis for controlling substitution patterns in these scaffolds. Further, the successful synthesis and isolation of regioisomerically pure compounds establishes a foundation for further exploration of their biological activities.